PENJADWALAN OPERASIONAL PEMBANGKIT BERBASIS ALGORITMA GENETIK PADA SISTEM PEMBANGKIT SUMATERA BAGIAN TENGAH - Rahmanul Ikhsan; Wati Ana Ratna Dwi; Budi Astuti (Teknoin, 2013)
Load demand of electric power supply varies from hour to hour in a day . It is inefficient to operate all power plants along day under various load variation. A power plant scheduling system is needed to minimize total operation cost of the power plants and in order to meet the amount of power needed by the load. This research proposes a method on power plant scheduling based on genetic algorithm. Total operation cost is used as objective function and the amount of power needed by the load is applied as a constraint. Population of chromosome in genetic algorithm represent candidates of alternative schedule of power plant operation. The best chromosome is the schedule with minimum cost and which meets the constraint. This method was applied to schedule the power plant system of Sumatera Bagian Tengah. Optimization was done in every 30 minutes. Based on test and analysis, this method results in more efficient cost, compared to manual operation of power plant systems.